2021
DOI: 10.3390/hydrology8040169
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Remote and In-Situ Data to Assess the Hydrological Response of a Post-Fire Watershed

Abstract: Forest fire is a common concern in Mediterranean watersheds. Fire-induced canopy mortality may cause the degradation of chemical–physical properties in the soil and influence hydrological processes within and across watersheds. However, the prediction of the pedological and hydrological effect of forest fires with heterogenous severities across entire watersheds remains a difficult task. A large forest fire occurred in 2017 in northern Italy providing the opportunity to test an integrated approach that exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…A 243-ha wildfire burned on southern aspects in late October—early November 2017 after leaves had senesced. In-situ post-fire surveys revealed a range of fire intensities and subsequent effects on soil and understory and overstory vegetation 41 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 243-ha wildfire burned on southern aspects in late October—early November 2017 after leaves had senesced. In-situ post-fire surveys revealed a range of fire intensities and subsequent effects on soil and understory and overstory vegetation 41 .…”
Section: Methodsmentioning
confidence: 99%
“…We selected eight fire-affected and eight control (unburned) beech trees from, respectively, a moderate burn severity area 41 and an unburned area about 500–1000 m apart at comparable elevations (Fig. 1 ; ~ 1100 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meteorological stations measured a cumulative rainfall in 13 hours, ranging between 41.4 mm (station 8097) and 83.0 mm (station 9105), except for the station 19335, which recorded 209.2 mm (Figure 2B). The corresponding return periods, estimated through the moving-window procedure for detecting the maximum rainfall depth observed for each duration (Norbiato et al, 2007) and then the Depth-Duration-Frequency curve (Folador et al, 2021), were approximately 4 years, except for the observations of station 19335 that registered a 300-years return period events. This fact was in accordance with the losses suffered (yellow dots in Figure 1).…”
Section: Flood Eventmentioning
confidence: 99%
“…Many studies provided evidence that the most severe sediment losses occurred within the first year after the wildfire [17][18][19]. However, the magnitude of the damages can vary depending on multiple factors, such as climate, fire frequency, soil type, geology, topography (especially slopes), and vegetation [20,21]. Regarding water quality, Rust et al [22] studied several sites in the western USA and found that nutrient flux (different forms of nitrogen and phosphorus), major-ion flux, and metal concentrations are the most common pollutants in streams within the first five years after a wildfire.…”
Section: Introductionmentioning
confidence: 99%